Somatic DICER1 mutations in adult-onset pulmonary blastoma. Issue 6 (28th April 2016) - de Kock, Leanne; Bah, Ismaël; Brunet, Joan; Druker, Harriet; Astigarraga, Itziar; Bosch-Barrera, Joaquim; Soglio, Dorothée Bouron-Dal; Nguyen, Van-Hung; Malkin, David; Priest, John R.; Foulkes, William D.
Several rare lung tumours morphologically mimic embryonal structures of the developing human lung. Historically, these blastomatous tumours were described under the umbrella term of pulmonary blastoma. Subsequently, distinct entities were recognised, such as childhood pleuropulmonary blastoma (PPB) [1] (International Classification of Diseases for Oncology (ICD-O-3) code 8973/3). Later, adult-onset pulmonary blastoma was separated into well-differentiated fetal adenocarcinoma (WDFA) (ICD 8333/3) and pulmonary blastoma (ICD 8972/3) [2]. Pulmonary blastoma is a biphasic epithelial and mesenchymal malignancy, whereas PPB is purely sarcomatous and WDFA is characterised by a monophasic immature epithelium. Since 1988, the childhood PPB has received particular attention because of 1) its unique developmental progression from relatively indolent neonatal-onset lung cysts, to aggressive cystic-solid and solid sarcomas by age 72 months; 2) PPB's status heralding a newly recognised familial tumour predisposition syndrome and 3) its strong association with both germ-line and somatic DICER1 mutations, which is not only true for PPB, but also for many other tumours in pleiotropic predisposition syndrome (now referred to as DICER1 syndrome). Until recently, neither WDFA nor pulmonary blastoma had been observed in families manifesting DICER1 syndrome [3]. However, in 2015, we identified a second somatic DICER1 RNase IIIb mutation [4] in a WDFA that arose in a 16-year-old germ-line DICER1 mutation carrier [5]. In addition to DICER1 mutations in PPB and WDFA, somatic CTNNB1 mutations (encoding β-catenin) appear to characterise WDFA and pulmonary blastoma [6], and are far less frequent in PPB [7, 8]. In contrast, TP53 mutations are found in both PPB [8] and pulmonary blastoma [9], but not WDFA [9]. We identified two somatic DICER1 mutations in each of two adult pulmonary blastomas, implicating DICER1 in causation http://ow.ly/10aM9V